Features of the reaction of the cardiovascular system to physical exercise in patients with pulmonary tuberculosis - S.A. Kalmykov; Yu.S. Kalmykova (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The aim is to study the response of the cardiovascular system to physical exercise in patients with infiltrative pulmonary tuberculosis. The features of adaptive capacity of the cardiovascular system was considered to physical stress on the results of the sample Martine-Kushelevskogo. The study involved 88 male and female patients with infiltrative pulmonary tuberculosis at the age of 21-35 years. Found that as a result of intoxication syndrome in pulmonary tuberculosis decrease adaptive capacity of the cardiovascular system. The positive effect of physical exercise on the studied parameters. The need to study the adaptive capacity of the cardiovascular system in these patients in order to correct and individualization of physical activity for each patient.